Active Fractions from Asparagus racemosus Willd. with Thrombolytic, Membrane Stabilizing and Free Radical Scavenging Activities (Bangladesh Pharmaceutical Journal, 2015)
Abstract not availableBangladesh Pharmaceutical Journal 18(2): 183-186, 2015